Rules, Contracts and Law Enforcement in the Ottoman Empire The Case of Tax-Farming Contracts - Altay, Bora; Oğuz, Fuat (Palgrave Studies in Institutions, Economics and Law, 2021)
IX, 116 p. 8 illus., 4 illus. in color.